42. CURRENT STATUS AND TRAINING NEEDS IN CONTINUING EDUCATION FOR NURSES AT VIETNAM GERMAN FRIENDSHIP HOSPITAL, 2025 (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe the current situation and the continuous training needs of nurses at Viet Duc University Hospital in 2025.Research methods: A cross-sectional study using a semi-structured questionnaire on 275 nurses at Viet Duc University Hospital.Results: The findings showed that the percentage of nurses who had participated in at least one continuous training course in the past two years was very high (97.8%). The blended learning format (a combination of in-person and online learning) accounted for the highest proportion among the training methods (56.5%). The training content focused on skills such as patient safety (86.5%), emergency care (80.4%), and communication skills (81.1%). The demand for training was high (96.7%), with essential skills identified as: emergency and urgent care skills, patient safety skills, communication skills, and professional practice skills in accordance with legal and ethical standards.Conclusion: Nurses actively registered for continuous training courses not only to meet professional practice requirements but also to enhance their clinical competence and soft skills in patient care.
Keywords: Continuous training; nurses; need for continuous training.